The ecological impacts of discarded cigarette butts. (February 2022) - Green, Dannielle S.; Tongue, Andrew D.W.; Boots, Bas
Abstract : Cigarette butts, one of the most littered items globally, present a unique challenge to ecosystems due to their ubiquity, persistence, and potential for harm. Over 35 studies have examined the toxicity of cigarette butts in biota from aquatic and terrestrial habitats from microbes to mice, but many organisms and habitats have not been tested. Two-thirds of studies are on aquatic organisms, and lethal effects were common. Research on the impacts on terrestrial life is lagging behind. Cigarette butts can affect the growth, behaviour, and reproductive output of individual organisms in all three habitats, but research on wider effects on biodiversity and ecosystem functioning is lacking. Here, we summarise the ecotoxicological concerns and identify important knowledge gaps for future research. Highlights: Littered cigarette butts are increasingly recognised as a unique and pressing ecotoxicological challenge. Since 2006, over 35 investigations have been made of the impacts of cigarette butts on aquatic and terrestrial life. Lethal impacts appear to be the most pronounced in aquatic systems, but less than a third of studies have examined effects in terrestrial biota. The majority (~80%) of studies have used cigarette butt leachate as opposed to the more environmentally realistic scenario of whole cigarette butts. Research on the impact of biodegradable cigarette butts is limited but suggests that they also pose a risk to the environment. Few studies have examined the wider ecological impacts of cigarette butts on population levels or species diversity, and there have been no studies on ecosystem functioning.